Food Safety Knowledge, Attitudes and Practices of Food Handlers along the Rice Value Chain of Uganda - Namubiru, Leatitiah; Male, Denis; Mukisa, Ivan Muzira; Byaruhanga, Yusuf Byenkya (Journal of Food Industry, 2024)
Food handlers play a critical role in controlling food contamination from “farm to fork”. Therefore, inadequate knowledge, poor attitudes and improper practices by food handlers pose a serious challenge to food safety. The aim of this study was to assess the knowledge, attitudes, and practices (KAP) of food handlers along the rice value chain of Uganda with the view of understanding factors that influence contamination of rice with aflatoxins, heavy metals and pesticides. A cross-sectional study, using a structured questionnaire through face-to-face interviews with 252 respondents was conducted in Butaleja, Gulu, Hoima, Kampala, Mutukula, Mbale and Mbarara districts. Categorical data was expressed as frequencies and percentages. The unique predictors of the KAP of rice handlers were defined using multivariate linear regression analysis. About 221 (87.7%) food handlers knew about the occurrence and causes of aflatoxins contamination in rice. Changes in colour (81.7%) and a musty smell (82.9%) were perceived to indicate the presence of aflatoxins. The main pre- and post-harvest aflatoxin preventative practices identified were growing resistant rice varieties (82.9%) and proper drying (79.8%). Food handlers were generally not knowledgeable (73.4%) about heavy metal contamination in rice. All food handlers used pesticides; however, 68.3% had never received formal training in pesticide use. Majority (86.1%) of food handlers were aware of the harmful effects of pesticides but on the contrary, this did not significantly change their practices towards safe pesticide use. At multivariate level, education was the unique predictor for aflatoxins and heavy metal contamination. Pesticide contamination was mainly influenced by district of residence. Therefore, appropriate educational programs organized to train food handlers can promote food safety in the rice value chain of Uganda. Interventions by regulatory agencies to strengthen enforcement of laws related to contaminants through regular surveillance at the farm and retail outlets are necessary to ensure compliance by food handlers.